Experiences of place-bound sociality amidst the COVID-19 pandemic: A qualitative analysis of environment-related coping strategies - Stadlmeier, Anna; Kremer, Dominik; Walker, Blake Byron (ERDKUNDE, 2022)
In the context of the COVID-19 pandemic, places of public encounter were effectively inhibited by lockdown regulations. In addition to several quantitative studies of the impact of the ongoing pandemic on society, little is known about the use of one’s spatial environment on individual coping strategies mitigating physical isolation. Through an explorative qualitative study we derived a typology of coping strategies that helped participants to balance responsible action and the urgent need for social contact.Our approach aligns with well-known theory in the field of place (Cresswell 2020) and place-bound sociality (cf. Schatzki 2002) in the context of phenomenology (Sloan & Bowe 2014, Rehorick 1991, Seamon 1979). Sixteen participants were selected reflecting diverse conceptualisation of community and representing socioeconomic and gender diversity in both urban and rural areas of the German state of Bavaria. Semi-structured interviews were conducted in the beginning of the second wave of COVID-19 restrictions from the end of November 2020 to early December, to reflect expectations and early routines associated with the isolation. In addition to social and individual, a variety of environment-related coping strategies can be observed. We (1) interpret those coping strategies, (2) discuss the essential function of places for the coordination and negotiation of social activities, and (3) relate the importance of public spaces to weak social ties (Granovetter1973) emphasising their outstanding value for individual wellbeing.